Radiological Staging and Management of the Periodontal Disease in Canines - Anjali, Kuraku; Raghunath, Mulinti; Prasad, Vaddadi Devi; Srinivas, Manda; Sreenu, Makkena (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Dental diseases are very prevalent in pet animals among which periodontal diseases are very common; by the two years of the age 80%  of the pets will be having one or the other dental disease. The periodontal disease is characterised by loss of tooth attachment and the  gingival recession. A total of 24 clinical cases were included in the study, in which complete oral cavity examination was carried out in an  anaesthetised patient to record the clinical signs. Dental radiography was done to record the percentage of attachment loss. Radiography  was taken in an anaesthetised animal by placing the cassette intra-orally for maxillary and mandibular incisors and canines, whereas for  premolars and molars of maxilla and mandible, patient was positioned laterally with slight elevation of head. Attachment loss appeared  as bone loss surrounding and across the tooth and this was calculated by measuring the alveolar margin from the cemento enamel  junction relative to the root length. Based on the attachment loss staging of the periodontal disease was done. Staging the periodontal  index helped in the treatment plans like chlorhexidine lavage, home care practices (tooth brushing, addition of dental treats, chews  and prophylactic antibiotic therapy), dental scaling and tooth extraction procedures.
Keywords: Dental radiography,; Dogs; Periodontal disease,; Periodontal index